Obstacles to Social Psychology in the Prevention of Tuberculosis (TB) in the City of Semarang - Supriyanto; Masrukhi; Astuti, Tri Marhaeni Puji (International Journal of Psychosocial Rehabilitation, 2020)
Social psychology is a form of personality related to one’s environment, education and behavior. The purpose of this study is to examine how the constraints of social psychology in the prevention of tuberculosis in the city of Semarang. The research method uses a qualitative approach with a phenomenological analysis method. This research was conducted in Kemijen Village, East Semarang District, Semarang City. The number of informants was four people consisting of 2 TB patients, 1 community leader and 1 TB activist. Data obtained by field observations ie researchers went directly to the study site to collect as much data as possible, in-depth interviews to explore as much information as possible from the informants and documentation of the activities of residents, patients and community leaders to strengthen the data. Findings in this study Lack of family and community support for TB patients can reduce patient motivation to seek treatment. Unhealthy behaviors such as smoking, staying up late, not paying attention to environmental cleanliness increases the risk of someone suffering from tuberculosis. The closed attitude of TB patients can potentially transmit to those around them. Negative stigma from the community causes TB patients to be closed with others.